Bewässerung in Pakistan: Zusammenstellung und Kommentierung neuester Daten - Scholz, Fred (ERDKUNDE, 1984)
The importance of irrigation for the agriculture of Pakistan is generally known. Reliable statistics about the current situation of irrigation in Pakistan are very rare. The present paper based on the latest unpublished material of the Water and Power Development Authority (WAPDA) in Lahore contains the current figures about the catchment areas of the Punjab rivers (Tab.1), their area irrigated by rivers (Tab. 2) and canals (Tab. 6), the monthly water flow of the rivers (Tab. 3), the dams, barrages and links (Tab. 4,7) as well as the agricultural acreage and the area affected by different stages of salinity (Tab. 8). These current figures show that the efforts and measures of the WAPDA in the last decades to improve the effectiveness of the irrigation system and to reduce the salinity of the soil have been successful. Here one example is given: From 1953-1975 the area affected by heavy salinity measured over 21700 km², dropping to only 13 200 km² during the period 1977-1979, whereas the nonsalinized area increased from 56% to 72% of the total agricultural acreage. This result and the successful extension of irrigation works were only possible owing to international aid and enormous efforts by Pakistan and will probably have a lasting effect only if international help continues.